Study to Assess the Maternal Factors Influencing Undernutrition among 3 to 6 Year Old Children of Davangere City - Ranjitha A; Navinkumar Angadi; DK Mahabalaraju (National Journal of Community Medicine, 2016)
Background: Nutritional status of children is an important indicator of health. Sociocultural and obstetric factors play an important role in the causation of under nutrition. In depth understanding of these factors is extremely necessary to formulate effective intervention strategy.